2012
DOI: 10.1111/j.1469-8137.2012.04058.x
|View full text |Cite
|
Sign up to set email alerts
|

Do thick leaves avoid thermal damage in critically low wind speeds?

Abstract: Summary• Transient lulls in air movement are rarely measured, but can cause leaf temperature to rise rapidly to critical levels. The high heat capacity of thick leaves can damp this rapid change in temperature. However, little is known about the extent to which increased leaf thickness can reduce thermal damage, or how thick leaves would need to be to have biological significance. We evaluated quantitatively the contribution of small increases in leaf thickness to the reduction in thermal damage during critica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
92
0
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(120 citation statements)
references
References 63 publications
2
92
0
7
Order By: Relevance
“…Despite the large within-site variation in LMA found at all points along the aridity gradient, there is a significant tendency for LMA to increase with aridity, perhaps because of the resistance to dehydration conferred by stiffer leaves (Niinemets, 2001;Wright and Westoby, 2002;Harrison et al, 2010) and/or the need for leaves to avoid overheating under transient conditions of high radiation load and low transpiration rates combined with low wind speed (Leigh et al, 2012). This increase in LMA is inevitably accompanied by an increasing structural N component.…”
Section: Leaf N and Environmentmentioning
confidence: 90%
“…Despite the large within-site variation in LMA found at all points along the aridity gradient, there is a significant tendency for LMA to increase with aridity, perhaps because of the resistance to dehydration conferred by stiffer leaves (Niinemets, 2001;Wright and Westoby, 2002;Harrison et al, 2010) and/or the need for leaves to avoid overheating under transient conditions of high radiation load and low transpiration rates combined with low wind speed (Leigh et al, 2012). This increase in LMA is inevitably accompanied by an increasing structural N component.…”
Section: Leaf N and Environmentmentioning
confidence: 90%
“…Desert plants are usually fully exposed to sunlight and rely on cooling by mainly radiative and sensible heat flux. In a recent study, Leigh et al [34] investigated the protective role of leaf heat capacity against thermal damage in four desert plant species during short periods with low wind speeds. They simulated leaf temperatures for 0.2 mm thick leaves in comparison to realistic leaves of 0.4–0.6 mm thickness and found that with thinner leaves, two out of the four species could become heat damaged.…”
Section: Discussionmentioning
confidence: 99%
“…New Phytologist Leigh et al, 2012). In particular, larger leaf size in warm-climate genotypes may be an adaptation that optimizes iWUE (Parkhurst & Loucks, 1972).…”
Section: Researchmentioning
confidence: 99%